Vector Mechanics for Engineers Statics - Beer, Ferdinand P.; Johnston, E. Russell; Mazurek, David F.; Sanghi, Sanjeev (McGraw-Hill, 2020)
A primary objective in a first course in mechanics is to help develop a student's ability first to analyze problems in a simple and logical manner and then to apply basic principles to their solutions. A strong conceptual understanding of these basic mechanics principles is essential for successfully solving mechanics problems. This edition of Vector Mechanics for Engineers will help instructors achieve these goals. Continuing in the spirit of its successful previous editions this edition provides conceptually accurate and thorough coverage together with a significant refreshment of the exercise sets and online delivery of homework problems to your students. The 12th edition has new case studies and enhancements in the text and in Connect. The hallmark of the Beer-Johnston series has been the problem sets.This edition is no different. Over 650 of the homework problems in the text are new or revised. One of the characteristics of the approach used in this book is that mechanics of particles is clearly separated from the mechanics of rigid bodies. This approach makes it possible to consider simple practical applications at an early stage and to postpone the introduction of the more difficult concepts. Additionally Connect has over 100 Free-Body Diagram Tool Problems and Process-Oriented Problems.